Long-term effectiveness of the midwifery initiated oral health-dental service program on maternal oral health knowledge, preventative dental behaviours and the oral health status of children in Australia. (17th February 2023) - George, Ajesh; Kong, Ariana; Sousa, Mariana S.; Villarosa, Amy; Ajwani, Shilpi; Dahlen, Hannah G.; Bhole, Sameer; Yaacoub, Albert; Srinivas, Ravi; Johnson, Maree
Abstract: Background: The Midwifery Initiated Oral Health-Dental Service was developed to train midwives to promote maternal oral health, and a large trial showed it substantially improved the oral health, knowledge and behaviours of pregnant women. Aim: Evaluate the long-term effectiveness of the program (post-trial) on maternal oral health knowledge, dental behaviours, and early childhood caries in offspring. Methods: A prospective cohort study involving 204 women and children 3–4 years (followed after trial) was conducted in Sydney, Australia from 2017 to 2019. Results: The program did not have a significant impact on the study measures. Mothers who received the program did have comparatively better knowledge around preventative behaviours to reduce early childhood caries and significantly more mothers were engaging in a key behaviour of using a cup to feed their child. Overall maternal oral health knowledge and level of education did have a protective effect on the dental decay of children. Higher knowledge and levels of education reduced the odds of having a dmft of one or more by over half (OR 0.473), and almost 80% (OR 0.212) respectively. Conclusions: Although the MIOH-DS program was not effective, there is still value in exploring other complementary interventions to improve maternal oral health, especially for disadvantaged families. Future research should focus on co-designing an antenatal and postnatal oral health intervention and exploring its long-term impact on the oral health of children.